Comparative Analysis of Basketball Training Systems in China and the United States: Implications for Enhancing Player Development and Competitive Levels - Chen Junpeng (Ilmu Inovasi Nusantara, 2024)
Despite various system reforms implemented by Yao Ming since becoming the president of the Chinese Basketball Association (CBA), the level of basketball competition in China has not shown significant improvement, indicating that underlying issues in the development of basketball in China remain unresolved. One of the main factors influencing the level of competition is the training system for players. This study aims to analyze and compare the training systems for basketball players in China and the United States, identifying the strengths and weaknesses of each system, including player selection, training, and management. The research employs both qualitative and quantitative approaches, using literature reviews, interviews with coaches and players, and direct observations of training programs. The results reveal that the training system in the United States is more structured, focusing on individual skill development from an early age, emphasizing basic techniques, game strategy, and physical conditioning, while also allowing players the freedom to develop according to their talents. Conversely, the system in China is more centralized and less flexible, with a greater focus on team achievements rather than individual development. The study's recommendations include increasing the focus on individual skill development from an early age, adopting elements from the American training system such as freedom in talent development and a more flexible training approach, enhancing the quality of coaches through more in-depth and continuous training, and creating a competitive environment that supports the development of young players. By implementing these recommendations, it is hoped that China can address the issues in its training system and improve the level of basketball competition both nationally and internationally